(untitled) (Bangladesh Journal of Child Health, 2021)
The commonest cause of respiratory distress in young children is bronchiolitis. Bronchiolitis is an acute viral lower respiratory tract infection which predominantly affects children up to two years of age. It is a seasonal disease, dominating winter months, with a peak over 6 to 8 weeks around the winter solstice. The evidence and guideline recommendations consistently support a clinical diagnosis with the limited role for diagnostic testing for children who present with the typical clinical features of viral upper respiratory infection progressing to the lower respiratory tract. Management is largely supportive, focusing on maintaining oxygenation and hydration. Evidence suggest no benefit from bronchodilator or corticosteroid use in infants with first episode of bronchiolitis. Evidence for other treatment such as hypertonic saline is evolving. In case of severe bronchiolitis, there is some role for high-flow nasal cannula and continuous positive airway pressure use. Bangladesh J Child Health 2020; VOL 44 (3) :161-169